L’explicit del De rebus bellicis: aspetti ideologici, giuridici e linguistici - Del Core, Vincenzo (Cultura giuridica e diritto vivente, 2020)
[The end of De rebus bellicis: ideological, juridical and linguistic aspects] The De rebus bellicis, probably written by an Anonymous member of the upper class who lived during the second half of the fourth century, represents a fundamental text to understand several aspects of the Late Antiquity, although, due to its not easy historical and literary collocation, it is a rarely mentioned work, even among scholars of law. As shown by the title, military themes constitute the framework of the treaty, however the concluding section is characterized by a brief, but meaningful mention of the juridical problems of the time: this contribution contains a proposal of analysis of these words.